PEMBELAJARAN DENGAN MODEL KOOPERATIF THINK PAIR SHARE DAN PENDEKATAN ILMIAH TERHADAP KEMAMPUAN SISWA DALAM PEMAHAMAN KONSEP DAN PEMECAHAN MASALAH PADA OPERASI BILANGAN BERPANGKAT DIKELAS X SMA N 1 TIGALINGGA T.P 2019/2020 - Sihite, Mariana (Jurnal Visi Eksakta, 2025)
This research includes experimental type research with a cooperative model. The population in this study were all tenth grade students at SMA Negeri 1 Tigalingga in the 2019/2020 school year which amounted to 5 classes, namely class X MIA1, class XMIA2, class XMIA3, class XMIA4, class X MIA5. This study aims to determine how learning should be with a cooperative model of think pair share and a scientific approach to students' ability to understand concepts and solve problems in the operation of power numbers in class X. The results of the study showed that the design of the learning model that had been designed was good to use. Based on Table 4.8, the results obtained tcount = 10.002 and ttable = 1.67 (tcount> ttable) which means Ha2 is accepted. Thus it can be concluded that learning with the Think Pair Share cooperative model is better than the scientific approach to understanding concepts on the operation of signed numbers in class X SMA Negeri 1 Tigalingga TP 2019/2020.